Isolation, Characterization and Activity of the Flowers of Rhododendron arboreum (Ericaceae). Issue 2 (2012) - Sonar, Pankaj Kumar; Singh, Ranjit; Khan, Shagufta; Saraf, Shailendra K.
Abstract : The flowers of Rhododendron arboreum have been reported to possess certain polyphenolic compounds. Thus, this study was aimed at the anti-microbial and phytochemical screening of the flowers. Important bioactive agents like steroids, saponins and flavonoids were detected in the flowers. Quercetin (a flavonoid) was isolated from the diethyl ether fraction of alcoholic extract by solvent-solvent extraction method. Isolated quercetin was identified and characterized by chemical tests, M.P., TLC, paper chromatography (with authentic marker) and spectroscopic methods like UV-Visible, FT-IR, 1 HNMR, 13 CNMR and Mass spectroscopy. The anti-microbial activity of the alcoholic and aqueous extract and isolated quercetin were investigated against five bacterial and two fungal strains by agar well-diffusion method. The activity was found to be concentration dependent. Ethanolic extract was found to be more active in comparison to the aqueous extract. Hence, isolation was done with ethanolic extract. The lowest effective concentration of quercetin was found to be 12.5 mg/ml against S. aureus and P. aeruginosa . Both extracts and isolated quercetin were found ineffective against fungal strains. Quercetin may be one of the components responsible for the observed anti-microbial activity of the plant.